APPLICATION OF CONTRA LEGEM IN JUDGE DECISIONS (Critical Study of Iddah Alimony Rights in Divorce Cases) - Maksum, Endang Ali; Suharto, S.; Khairuddin, K.; Zuhraini, Z.; Susanto, Is (SMART: Journal of Sharia, Traditon, and Modernity, 2021)
The subject of this study is based on article 149 letters (b) Compilation of Islamic law which reads: ex-husband must provide maintenance, maskan, and kiswah to ex-wife during the iddah, unless the ex-wife has been granted talaq bain or nusyuz and is not pregnant. There are two barriers for an ex-wife to earn a living during the period of iddah, namely because the wife is divorced ba'in and or because the ex-wife is nusyuz. In general, the wife filed for divorce in court because she could no longer stand her husband's treatment of her. As a result of the law, if the wife who filed for divorce sues the Court, then the panel of judges will issue a divorce. Unless the husband violates the talaq. In the context of the wife falling into the act of nusyuz, generally as a result of the treatment and conduct of the husband towards the wife. If this is returned to the sound of the law then it will be very felt the injustice received by the wife (ex-wife). This study seeks to find the answer from the formulation of the problem "Why is contra legem important for the judge in deciding the case (inconcritoplaintiff) divorce with the decision of talaq ba'in and or proven in court nusyus wife's arbitrary because of the husband treatment of his wife? Materials and data are obtained by methods library research, the nature of the research is normative research. The goal to be achieved is to provide an alternative solution in providing justice and legal protection to women (ex-wives) who do not get iddah alimony because of filing a lawsuit or nusyus with a theory approach contra legem. Positive law in practice is not sufficiently able to accommodate the legal facts revealed in the Court, in another narrative it can be said that positive law always lags behind social reality. So in the legal system in Indonesia, the judge's ijtihad to deviate and or find the law is accommodated by the principle of Contra legemin order to provide justice and benefits to the community seeking justice, the judge needs to do contra legem.Keywords: Contra Legem; Iddah Livelihood; Divorce Lawsuit; Judge's Decision